The Fin-de-Siècle World - Saler, Michael (Routledge Worlds, 2015)
This comprehensive and beautifully illustrated collection of essays conveys a vivid picture of a fascinating and hugely significant period in history, the Fin de Siècle. Featuring contributions from over forty international scholars, this book takes a thematic approach to a period of huge upheaval across all walks of life, and is truly innovative in examining the Fin de Siècle from a global perspective. The volume includes pathbreaking essays on how the period was experienced not only in Europe and North America, but also in China, Japan, the Middle East, Latin America, Africa, India, and elsewhere across the globe. Thematic topics covered include new concepts of time and space, globalization, the city, and new political movements including nationalism, the "New Liberalism", and socialism and communism. The volume also looks at the development of mass media over this period and emerging trends in culture, such as advertising and consumption, film and publishing, as well as the technological and scientific changes that shaped the world at the turn of the nineteenth century, such as the invention of the telephone, new transport systems, eugenics and physics. The Fin-de-Siècle World also considers issues such as selfhood through chapters looking at gender, sexuality, adolescence, race and class, and considers the importance of different religions, both old and new, at the turn of the century. Finally the volume examines significant and emerging trends in art, music and literature alongside movements such as realism and aestheticism. This volume conveys a vivid picture of how politics, religion, popular and artistic culture, social practices and scientific endeavours fitted together in an exciting world of change. It will be invaluable reading for all students and scholars of the Fin-de-Siècle period.